Crystal structures of [μ2-(Ra,Sa,3aR,7aR)-1,3-bis(2,7-dicyclohexylnaphthalen-1-yl)octahydro-1H-benzo[d]imidazolidin-2-ylidene]chlorido(η4-1,5-cyclooctadiene)iridium dichloromethane monosolvate and [μ2-(Sa,Sa,3aR,7aR)-1,3-bis(2,7-dicyclohexylnaphthalen-1-yl)octahydro-1H-benzo[d]imidazolidin-2-ylidene]chlorido(η4-1,5-cyclooctadiene)iridium - Stephen A. Moggach; Brian W. Skelton; Daven J. Foster (Acta Crystallographica Section E: Crystallographic Communications, 2020)
The title compounds, [Ir(C51H64N2)Cl(C8H12)]·CH2Cl2, (I), and [Ir(C51H64N2)Cl(C8H12)], (II), represent the first two examples of hexahydrobenzoimidazole-based N-heterocyclic carbene (NHC) iridium complexes. The diastereomeric complexes differing only in their axial chirality, which could be separated via column chromatography, show noticeable differences in their 1H NMR spectra. Compound (I) crystallizes in the monoclinic system (P21) with two independent complexes and two half-occupied dichloromethane molecules in the asymmetric unit, while compound (II) crystallizes in the orthorhombic system (P212121) with one complex in the asymmetric unit. The fused five-membered N-heterocycles of NHCs show unusually high backbone torsion angles of −34.1 (5) and −30.9 (5)° for (I) and −31.5 (7)° for (II), but the Ir—Ccarbene bond lengths of 2.046 (6) and 2.021 (6) Å for (I) and 2.045 (8) Å for (II) present typical NHC—Ir bond lengths. The solvent molecule in the crystal of (I) was found to be highly disordered and its contribution to the scattering was masked using the solvent-masking routine smtbx.mask in OLEX2 [Dolomanov et al. (2009). J. Appl. Cryst. 42, 339–341]. The solvent contribution is not included in the reported chemical formula and other crystal data.